Phase I/II Pilot Study of Wilms' Tumor 1 Peptide‐Pulsed Dendritic Cell Vaccination Combined With Conventional Chemotherapy in Patients With Head and Neck Cancer. Issue 3 (6th June 2019) - Ogasawara, Masahiro; Miyashita, Mamiko; Yamagishi, Yuka; Ota, Shuichi
Abstract: The prognosis of metastatic or relapsed head and neck squamous cell carcinoma (HNSCC) remains poor despite the introduction of immune checkpoint blockade agents. We aimed to investigate the safety and the feasibility of a vaccination with Wilms' tumor 1 peptide‐loaded dendritic cells (DCs) and OK‐432 adjuvant combined with conventional chemotherapy. Eleven eligible patients with metastatic or relapsed HNSCC were enrolled. No severe adverse events related to a vaccination were observed. Five patients had durable stable disease and six other patients had disease progression after DC vaccination. Median progression‐free survival and overall survival was 6.4 months and 12.1 months, respectively. DC vaccination augmented Wilms' tumor 1‐specific immunity which might be related to clinical outcome. These results indicate that DC‐based immunotherapy combined with a conventional chemotherapy is safe and feasible for patients in advanced stage of HNSCC.